Clinical and pathological features of 124 patients with indistinguishable sellar lesions and central diabetes insipidus. (October 2020) - Wang, Zhicheng; Zhu, Jianyu; Yao, Yong; Zhu, Huijuan; Deng, Kan; Lu, Lin; Zhang, Yi; Duan, Lian; Wang, Linjie; Yang, Hongbo; Xiao, Yu; Zhao, Dachun; et al.
Highlights: It's difficult to identify the etiology of sellar lesion by noninvasive examination. Germ cell tumor should be considered firstly when patient is young. Endoscopic transsphenoidal biopsy is relatively safe and effective. Abstract: Background: Sellar lesions with central diabetes insipidus have a wide range of causes, and diagnosis is relatively difficult. The indication and clinical value of biopsy are still controversial. Objective: To describe the etiology, demographic characteristics, manifestations, laboratory tests and imaging findings of this disease and to explore the clinical value and safety of endoscopic transsphenoidal biopsy. Methods: Retrospective analysis of 124 patients with sellar lesions and central diabetes insipidus who underwent endoscopic transsphenoidal biopsy at the Neurosurgery Department, Peking Union Medical College Hospital, from 2011 to 2019. Results: The main etiology includes congenital diseases, inflammatory/infectious diseases and tumor diseases. The most common diseases were germ cell tumors, Langerhans cell histiocytosis, lymphocytic hypophysitis, and Rathke's cleft cysts. Except for the age at the time of biopsy of patients with tumor diseases, which was significantly lower than that of the other two, the other clinical manifestations of the three types of diseases were not significantly different. Among the 124 patients, biopsy was performed via an endoscopic transsphenoidal approach for 101 with intrasellarly available lesions or via an endoscopic extended transsphenoidal approach for 23 with intrasellarly unavailable lesions. 6 patients had central nervous system infections after surgery, and 3 had cerebrospinal fluid rhinorrhea, of which 2 were surgically repaired. These incidences were basically the same as those of classic surgery. 2 patients had worse visual acuity, 2 had worse visual field, and 2 had worse eye movement. Excepting one patient, all of whom have recovered after treatment. Conclusions: Noninvasive examination is difficult for identifying the common causes of this type of disease. Endoscopic transsphenoidal biopsy is relatively safe and effective, helps doctors to select the best treatment for patients, and is worth promoting.